2016
DOI: 10.1152/ajpheart.00610.2015
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex failure increases the risk of pulmonary edema in conscious rats with normal left ventricular function

Abstract: In heart failure with preserved ejection fraction (HFpEF), the complex pathogenesis hinders development of effective therapies. Since HFpEF and arteriosclerosis share common risk factors, it is conceivable that stiffened arterial wall in HFpEF impairs baroreflex function. Previous investigations have indicated that the baroreflex regulates intravascular stressed volume and arterial resistance in addition to cardiac contractility and heart rate. We hypothesized that baroreflex dysfunction impairs regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Additionally, they demonstrated that high salt intake exacerbates such volume intolerance (Sakamoto et al . ).…”
Section: Structural and Functional Organization Of The Cardiac Nervoumentioning
confidence: 97%
See 3 more Smart Citations
“…Additionally, they demonstrated that high salt intake exacerbates such volume intolerance (Sakamoto et al . ).…”
Section: Structural and Functional Organization Of The Cardiac Nervoumentioning
confidence: 97%
“…Sakamoto et al . () demonstrated that sinoaortic denervation, which is an established animal model of impaired baroreflex, destabilizes left atrial pressure dynamics along with arterial pressure regulation in freely moving rats, thereby inducing recurrent episodes of high left atrial pressure. Additionally, they demonstrated that high salt intake exacerbates such volume intolerance (Sakamoto et al .…”
Section: Structural and Functional Organization Of The Cardiac Nervoumentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we also demonstrated that baroreflex failure with salt loading caused a transient increase in LAP of normal rats. 24) Sakamoto, et al clearly demonstrated that baroreflex modulates both cardiac function and vascular function to regulate AP and that baroreflex-induced changes in vascular resistance and stressed blood contribute to AP regulation far greater than changes in contractility and heart rate. 25) These results strongly suggest that baroreflex failure could induce volume intolerance independent of left ventricular systolic function, and that baroreflex failure would be the main cause of flash pulmonary edema in HFpEF.…”
Section: 14-17)mentioning
confidence: 99%